Znotrajjezikovni in/ali medjezikovni dejavniki oblikotvornih sprememb v slovenskem zgodovinskem oblikoslovju - Orel, Irena (Jezikoslovni zapiski, 2013)
This article substantiates the relationships between fixed and variable elements in the history of (standard) Slovenian, presents a typology of doublets with regard to various factors that give rise to them, and examines individual analogical changes in inflectional patterns in the standard and nonstandard form of the language. Some changes that have been attested in individual Slavic languages can also be explained through sociolinguistic interlinguistic influences.
Keywords: analogy; historical morphology; inflection; language variation; morphology; oblikoslovje; Slovene; Slovene langauge; slovenščina; sociolinguistics; sociolingvistika; zgodovinsko oblikoslovje